KORELASI POLARISASI ELEKTRO-OPTIS DENGAN KOMPOSISI ASAM LEMAK PADA MINYAK ZAITUN SEBAGAI METODE UJI ALTERNATIF MUTU MINYAK GORENG - Nurhasanah, W Dewi; Sugito, Heri; Richardina, Very; Azam, Much; Firdausi, Ketut Sofjan (BERKALA FISIKA, 2019)
In this study the quality of olive oil which has been degraded due to heating has been tested using the electro-optical transmission polarization method. The light source used was a laser pointer with Î» = 650 nm. The degradation of the quality of olive oil was measured to be based on changes in the electro-optical polarization angle, while changes in the composition of fatty acids were tested using Gas Chromatography and Mass Spectroscopy (GCMS). The results showed that the polarization angle increases in second order polynomial on the increase in voltage and linearly on the heating duration in the sample which showed a decrease in the quality of homogeneous olive oil. Assuming that the polarization change is a linear combination of the main fatty acids from olive oil, it is obtained that C19:2 and C19:0 fatty acids are the most contributing to oil quality, that is, the reduction in oil quality is indicated by increasing polarization which is accompanied by an increase in C19:0 fatty acids and a reduction in C19:2 fatty acids. Whereas specifically for electro-optical polarization, in addition to C19:2 and C19:0 fatty acids, C19:1 also appears which slightly increases polarization by increasing the fatty acid. This method can be developed further for investigation into other vegetable oils, as well as evaluating halal oil due to contamination of lard.Keywords: Electro-optical polarization, olive oil, fatty acid composition, change inpolarization angle